FUNGSI ANGGARAN SEBAGAI ALAT KEBIJAKAN DALAM PENGEMBANGAN SENI DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA BANDUNG - Fathonah, Silvia; Umam, Khaerul; Wahyu, Fitri Pebriani (Jurnal Ilmu Administrasi Negara (JUAN), 2022)
This research was conducted at the Department of Culture and Tourism of the city of Bandung. By using a qualitative approach and descriptive research methods. The Department of Culture and Tourism of the city of Bandung as the government agency responsible for policies regarding the art development program has a main program carried out, namely a coaching program for art institutions. This program policy is a routine and priority program policy for the Bandung City Culture and Tourism Office. The budget owned by the department of 25% is allocated to programs related to arts, this makes a large enough budget to function well or not in the implementation of program policies. The results of the study indicate that the existing budget function for this art development program policy can be said to be ineffective, in which the problems that occur are still the same when the budget has not been reduced and after there has been a budget reduction. This needs to be evaluated and reviewed by the service so that the objectives of the arts development program policy can be achieved and a large enough budget can function to direct program policies with good results.